Polymorphism of PPM1K Gene and The Association Related to Retail Indonesian Sheep Meat Cuts - Suhendra, Muhammad; Ratna Sholatia Harahap; Kasita Listyarini; Cece Sumantri; Cahyo Budiman; Katrin Roosita; Gunawan, Asep (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2024)
The PPM1K (Protein Phosphatase, Mg2+/Mn2+ Dependent 1K) gene is assumed to associate with retail meat cuts. This study aims to determine the association of the PPM1K gene polymorphisms with retail meat cuts among various breeds of Indonesian sheep. The Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) approach was used to determine the polymorphisms of the PPM1K gene in 130 Indonesian rams aged 10-12 months with body weights ranging from 20-25 kg. The association study between PPM1K and retail meat cuts was analyzed using General Linear Model (GLM). The research showed that the PPM1K gene was polymorphic, with three genotypes: AA (458 bp), GG (259 bp and 199 bp), and AG (458 bp, 259 bp, and 199 bp). The PPM1K gene polymorphisms were significantly (P<0.05) associated with breast cut, which is the breast muscle and bone. The GG genotype of the PPM1K gene had a higher value on breast lamb. This result implies that the PPM1K gene could be a potential candidate for marker-assisted selection for improving the lamb quality of Indonesian sheep.